Smart Social Media Education: Preventing Hoaxes and the Spread of False Content Among Vacational High School Student - Simorangkir, Melda; Sinaga, Dameria; Susilo, Susilo; Male, Hendrikus; Ditasona, Candra; Kristina, Nugra Heni (Fakultas Keguruan dan Ilmu Pendidikan-Universitas Timor, 2025)
The spread of hoakses in Indonesia continues to rise, as recorded by the Ministry of Communication and Informatics (Kominfo), with more than 770 hoakses identified between August 2018 and February 2019. This phenomenon indicates that hoakses pose a serious threat, requiring continuous education and intervention efforts. Therefore, this Community Service Program (PKM) aims to enhance students' digital literacy in recognizing, identifying, and countering fake news on social media. The workshop was conducted at SMKN 1 Klaten, involving 120 twelfth-grade students from the multimedia department. The method used in this program was an interactive workshop that included education on hoakses, practical exercises in identifying false information, and discussions on the social impact of hoaks dissemination. Through this activity, students were equipped with the skills to become critical and responsible consumers of information in the digital era. The training, which lasted for five class hours, successfully engaged students, as evidenced by the numerous questions that arose throughout the session. It is hoped that this initiative will contribute to creating a safer digital environment and support government efforts to improve digital literacy among the younger generation.